Repositioning of the UM Pancasila Laboratory: Building a Center of Excellence for Multicultural and Local Excellence in the Digital Era - Aminulloh, Akhirul; Wijayanti, Febry; Widodo, Wahyu; Ayudha, Nora Titahning (Universitas Tribhuwana Tunggadewi, 2025)
Pancasila as the basis of the state and the ideology of the Indonesian nation plays a central role in maintaining national integration and social diversity. However, in today's digital and globalization era, Pancasila values face serious challenges, especially among the younger generation. The massive flow of information, the development of transnational ideologies, and the dominance of individualistic culture have led to a disorientation of values, so that the relevance of Pancasila as a guideline for life has begun to be questioned. This study aims to analyze the strategic repositioning of the Pancasila Laboratory (Lapasila) of the State University of Malang in responding to the challenges of ideological and social disruption, as well as exploring its potential as a center of excellence in science and technology in the field of Pancasila, multiculturalism, and local wisdom. Using a qualitative approach with data collection techniques in the form of in-depth interviews with internal stakeholders, this study found that Lapasila has significant historical strength, academic legitimacy, and digital potential. However, internal weaknesses such as weak institutional management, low research productivity, and lack of digital strategies are the main obstacles. Meanwhile, external opportunities such as national policy support, public needs for ideological references, and digital media space can be used to the fullest. This study recommends the repositioning of Lapasila through digital transformation, interdisciplinary approaches, strengthening collaborative networks, and innovation-based institutional reform. Thus, Lapasila can play a strategic role in the actualization of Pancasila values in a contextual and sustainable manner in the midst of the dynamics of a multicultural society.Pancasila sebagai dasar negara dan ideologi bangsa Indonesia memiliki peran sentral dalam menjaga integrasi nasional dan keragaman sosial. Namun, di era digital dan globalisasi saat ini, nilai-nilai Pancasila menghadapi tantangan serius, terutama di kalangan generasi muda. Arus informasi yang masif, berkembangnya ideologi transnasional, serta dominasi budaya individualistik telah menyebabkan disorientasi nilai, sehingga relevansi Pancasila sebagai pedoman hidup mulai dipertanyakan.Penelitian ini bertujuan untuk menganalisis reposisi strategis Laboratorium Pancasila (Lapasila) Universitas Negeri Malang dalam merespons tantangan disrupsi ideologis dan sosial, serta mengeksplorasi potensinya sebagai pusat unggulan ilmu pengetahuan dan teknologi di bidang Pancasila, multikulturalisme, dan kearifan lokal. Dengan menggunakan pendekatan kualitatif dan teknik pengumpulan data berupa wawancara mendalam dengan para pemangku kepentingan internal, penelitian ini menemukan bahwa Lapasila memiliki kekuatan historis, legitimasi akademik, dan potensi digital yang signifikan. Namun, kelemahan internal seperti lemahnya manajemen kelembagaan, rendahnya produktivitas riset, dan kurangnya strategi digital menjadi hambatan utama. Sementara itu, peluang eksternal seperti dukungan kebijakan nasional, kebutuhan publik terhadap referensi ideologis, serta ruang media digital dapat dimanfaatkan secara optimal.Penelitian ini merekomendasikan reposisi Lapasila melalui transformasi digital, pendekatan interdisipliner, penguatan jejaring kolaboratif, serta reformasi kelembagaan berbasis inovasi. Dengan demikian, Lapasila dapat memainkan peran strategis dalam aktualisasi nilai-nilai Pancasila secara kontekstual dan berkelanjutan di tengah dinamika masyarakat multikultural.Â